Towards a progressive EMU fiscal governance - Nacho Álvarez Peralta; Georg Feigl; Nasos Koratzanis; Markus Marterbauer; Catherine Mathieu; Tom McDonnell; Laura Pennacchi; Christos Pierros; Henri Sterdyniak; Achim Truger; Jorge Uxó González (European Trade Union Institute (ETUI), 2019)
The fiscal governance of the EMU is in dire need of reform. Its current arrangements suff er from several shortcomings, most notably, the limitations they impose on national fiscal policies, steering them towards too restrictive or pro-cyclical stances; the absence of an unconditional lender of last resort for governments and the consequent doubts over the 'safe asset' status of national government bonds that this absence creates; the underdevelopment of an economic (policy) union, resulting in the dominance of public deficit and debt considerations over considerations of well-being, full employment and broader economic objectives in guiding the conduct of fiscal policies; and last but not least, the fact that, under the EMU institutional architecture, there are fewer opportunities for democratic participation and scrutiny of the conduct of fiscal policies. Starting from the view that the crises in the euro zone were basically triggered by financial markets and reinforced by a lack of instruments for effective economic policy at the EMU level, we contribute to the ongoing debate on how to reform the Eurozone. We propose a focus on general principles for fiscal governance reform aiming at a better economic, social and environmental performance on the part of EMU. As the main principles for progressive governance, we identify a need for: - a much more active and prominent role for fiscal policy; - 'safer' government bonds; - more and better coordination between fiscal and other economic, social and environmental policies, as well as between member states, to foster sustainable well-being; and - more democratic participation and scrutiny.
Keywords: 330; financial crisis; euro zone; financial reform; EU countries; Finanzkrise; Eurozone; Finanzreform; EU-Staaten